Menggunakan 'Penta-Helix' untuk Menjembatani Reaksi Masyarakat Terhadap Vaksin Covid-19 - Zamruddin Hasid; Adi Wijaya; Arfiah Busari; Erwin Kurniawan A. (Jurnal Pengabdian Pada Masyarakat, 2022)
USİNG AN ‘PENTA-HELİX’ TO BRİDGE THE PUBLİC'S REACTİON TO THE COVİD-19 VACCİNE. The response to the SARS-CoV-2 disaster calls for worldwide attention. This paper creates attributes in the ‘Penta-Helix’ that reflect pandemic prevention procedures. In order to run optimally, the enterprise strategy model makes it easier for the government to move the vaccine program. We explained critical exploration and focus group discussions (GFD) by the roles of the other four parties, namely academics, business, media, and community (A-B-G-M-C). The cluster at the ‘Penta-Helix’ mapped out and shared responsibilities in solidarity. Initially, performing this concept was determined academically, where the talents of skilled scholars were tested by studying findings relevant to the pandemic. The second step is business. Their position influences the production of vaccines, their distribution, and the price of medical devices for the public. Then, the fourth partner is tasked with limiting and filtering misinformation, especially vaccines. The benchmark for ‘herd immunity’ is how enthusiastic the public is about the popularity of the vaccine. Provision of vaccines in sufficient quantities is clear evidence that the government is convincing the community to follow the vaccination directions. Critical analysis puts forward the front line, actually based on the public spirit. The ‘Penta-Helix’ mechanism indicates a sustainable action plan. Future scenarios consider tactical managerial decisions.